Performance Analysis of Small Horizontal Axis Wind Turbine with Airfoil NACA 4412 - Widiyanto, Syam; Sasongko Pramonohadi; Mohammad Kholid Ridwan (Publisher Cv. Inara, 2021)
The horizontal axis wind turbine (HAWT) design with low wind speed requires blade geometry selection. The analysis uses the potential flow panel method and the integral boundary layer formulation to analyze wind flow around the airfoil. The blade design with the blade element momentum (BEM) theory has an aerodynamic coefficient value along the blade. Power wind calculates to model the wind shear pressure at each blade. This research aims to determine the wind turbine rotor based on the performance, including the power coefficient, tip speed ratio, power, and rpm. The simulation uses an airfoil NACA 4412 which has optimal coefficient lift (Cl) = 1.92 at 190 pitch of angle, coefficient drag (Cd) = 0.0635 at 130 pitch angle and Cl / Cd = 155 at tilt angle = 40. Five models of 2.5 m diameter blades with different angles for each chord. The test results show that the change in the speed ratio affects the power coefficient so that the optimal power coefficient on NACA 4412 in experiment 5 is 0.56, and change in rotation per minute affects the output power so that the rotation per minute and the optimal power in experiment 4 with a value of 374 rpm and 553 W.